Development of a novel filtered cathodic vacuum arc deposition system for carbon metal nanocluster thin films - Xu, Naiyun (2014)
Carbon metal nanocluster (C:Me) films have been used to protect the metal nanoclusters from oxidation and enhance its properties, in the same time the incorporation of metal nanoclusters within the carbon thin film is also able to reduce the high compressive stress of the carbon film, improve its mechanical, electrical properties. However, the conventional deposition methods to synthesize C:Me nanoclusters film still have difficulties in controlling the density of metal nanoclusters, and the metal content, etc. Hence, a better deposition method is desired to meet these requirements. In this thesis, a novel Y-shaped magnetic filters and anti-Helmholtz focusing coil is specially designed and implemented on the filtered cathodic vacuum arc (FCVA) deposition system. By using the Y-bend FCVA deposition system, two streams of plasma can be generated simultaneously, which is able to deposit C:Me nanocluster film. The ways to control the microstructure and property have been explored, such as magnetic trap generated by the anti-Helmholtz focusing coil which can be used to control the metal cluster density, arc current and growth temperature which can affect the film microstructure. Other than the deposition parameters, influence of post treatment such as thermal and laser annealing has also been studied. In addition, the electrical, tribological properties and applications of carbon based thin film have also been investigated. This thesis also reports on the growth of carbon nanotubes (CNTs) on C:Me nanocluster films such as C:Co nanocluster, which can be used as carbon hybrid system. The C:Co nanocluster film deposited using a 500°C growth temperature shows electrical conducting behavior, which can be used to eliminate the use of insulating barrier layer used in conventional CNTs growth.